2018
DOI: 10.5005/jp-journals-10024-2301
|View full text |Cite
|
Sign up to set email alerts
|

Crestal Bone Loss around Dental Implants: Platform Switching vs Platform Matching—A Retrospective Study

Abstract: The crestal bone around the implants can be preserved with platform-switching concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The tendency for vertical and horizontal marginal bone losses for the PS dental implants reduced over time, which was consistent with the results of a previous study [ 24 ]. However, with extended observation time, both PS and PM dental implants exhibited matching results in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The tendency for vertical and horizontal marginal bone losses for the PS dental implants reduced over time, which was consistent with the results of a previous study [ 24 ]. However, with extended observation time, both PS and PM dental implants exhibited matching results in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…A 12-month retrospective study found that the mean vertical crestal bone level for PS dental implants was 2.16 ± 1.02 mm (range, 2.16–3.12 mm), whereas the average for PM dental implants was 1.55 ± 0.82 mm (range, 1.55–4.18 mm) of crestal bone loss. In addition, the mean horizontal crestal bone level for PS dental implants was 2.27 ± 0.91 mm, whereas the mean crestal bone level was 2.16 ± 0.77 mm for the PM dental implants [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 ] In spite of the high success rate, crestal bone loss has been a concern for many clinicians. [ 4 5 ] In the past, 1.5 mm bone loss in the crestal region in the early years and 0.2 mm in the next consequent years were considered normal. [ 6 7 ] However in regions with poor bone quality, losing that vital bone with reduced bone height is of major concern.…”
Section: Introductionmentioning
confidence: 99%